Expression and functional analysis of endothelial nitric oxide synthase (eNOS) in human placenta. - Rossmanith, W; Hoffmeister, U; Wolfahrt, S; Kleine, B; McLean, M; Jacobs, R; Grossman, AB (1999)
We have investigated the expression and localization of endothelium-derived nitric oxide synthase (eNOS) and the effect of eNOS on placental human chorionic gonadotrophin (HCG) release. eNOS mRNA was found to be expressed in all tissues, with its expression significantly (P<0.05) increased across gestation. Compared to normal term gestation, placentae from term pregnancies with fetal retardation, or maternal diabetes, but not with maternal hypertension, displayed significantly more (P<0.05) eNOS mRNA. By immunocytochemistry, we found staining for eNOS in both the cyto- and syncytiotrophoblasts of first trimester and a loss of cytotrophoblast eNOS staining in term placentae, while syncytiotrophoblasts at term were strongly eNOS positive. Additional staining was found in endothelium surrounding the vascular tree. HCG was found to colocalize with eNOS in trophoblasts, but not in endothelia. When placental explants were perifused, exposure to the NOS substrate, the NO donor, I-arginine and trinitroglycerol evoked a prompt, albeit transient, increase of HCG release. The NOS inhibitor delayed, but did not block arginine-induced HCG release. Thus, eNOS is expressed in the human placenta at increasing levels during gestation with further increases during some pathological conditions. A role for NO in the acute endocrine modulation of the placenta is suggested by the colocalization of eNOS with HCG in human trophoblasts and the prompt secretion of HCG in response to agents which increase NO concentrations.